The effect of isolation time to the thermal degradation of cellulose nanofiber (CNF) and carboxymethyl cellulose nanofiber (CM-CNF) / Abdul Hafidz Mohd Raffe - Mohd Raffe, Abdul Hafidz (Faculty of Applied Sciences, 2017)
In this study, oil palm empty fruit bunch OPEFB fiber biomass was pre-treated using sodium hydroxide (NaOH) and bleaching. The cellulose nanofiber was isolated by alkali treatment with different isolation time (2,4 and 6 hours) and sonicate at 55 ºC for 3 hours. The carboxymethyl cellulose nanofiber (CM-CNF) was synthesized using two steps that is alkalization using 20% of NaOH and etherification using monochloroacetic acid (MCA). The CNF and CM-CNF obtained were characterized using Attenuated Total Reflectance Fourier Transform Infrared (ATR-FTIR) spectroscopy, Ultraviolet visible (UV-Vis) spectrophotometer and Thermalgravimetric Analyzer (TGA). result obtained shows that the CNF isolated for 2 hours has a highest percentage yield which is 20.40 % while there is no major different in percentage yield for the CM-CNF synthesized. From the FTIR spectra obtained, the peaks at 1700 cm-1 and 1200 cm-1 of hemicellulose and lignin were efficiently removed after bleaching process while for CM-CNF, the peak around 1600 cm-1 was appeared represent carboxylate (COO-) group. The determination of nano size in CNF was determine using UV-Vis spectroscopy. Result show that the percentage transmittance for the isolated CNF is more than 95 % at wavelength of 600 nm. From the TG curve obtained, it shows that all samples has a three phases of degradation. The onset degradation temperature for bleached OPEFB is lower than the raw OPEFB due to the removal of hemicellulose and lignin. The CNF isolated for 4 hours has a good thermal stability with the degradation temperature of 311.81 ºC and the production of CM-CNF has high thermal stability compared to the CNF isolated.